2012
DOI: 10.1111/j.1365-2915.2012.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and electrophysiological responses of females of two species of tabanid to volatiles in urine of different mammals

Abstract: Urine volatiles from different ungulates (cows, horses and sheep) were tested as bait for tabanids in southeastern France using Nzi traps during the early summer of 2011. Tabanus bromius Linnaeus, 1758 and Atylotus quadrifarius (Loew, 1874) (both: Diptera: Tabanidae) were the most captured species, respectively representing 57% and 41% of all tabanids collected (all of which were female). Horse urine significantly increased catches of T. bromius (1.6-fold) and A. quadrifarius (3.5-fold), and sheep urine signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 53 publications
(78 reference statements)
1
26
0
Order By: Relevance
“…and Hybomitra spp. (Diptera: Tabanidae) in North America and in Europe (Krcmar et al ., ; Mihok & Mulye, ; Baldacchino et al ., ). The synergism between ammonia and phenols demonstrated for Hybomitra spp.…”
Section: Introductionmentioning
confidence: 97%
“…and Hybomitra spp. (Diptera: Tabanidae) in North America and in Europe (Krcmar et al ., ; Mihok & Mulye, ; Baldacchino et al ., ). The synergism between ammonia and phenols demonstrated for Hybomitra spp.…”
Section: Introductionmentioning
confidence: 97%
“…Chrysops Hybomitra Browne and Bennett, 1980 Tabanus abactor Philip Moor et al, 1996Fischer 2006 72 Blahó et al, 2013Horváth et al, 2008 e.g. Swynnerton, 1933;Lloyd, 1935Hassanali et al, 1986Bursell et al, 1988;Madubunyi et al, 1996 Canopy trap Krčmar et al, 2006 Canopy trap 6.4 Krčmar and Lajoš, 2011Baldacchino et al 2012Reeves, 1951 e.g. Fallis and Smith, 1964;Nelson, 1965;Knox andHays, 1972 Wilson et al, 1966;DeFoliart and Morris, 1967;Everett and Lancaster Jr., 1968 Hribar et al, 1992;Kristensen and Sommer, 2000;Mihok and Lange, 2012 1-octen-3-ol Vale and Hall, 1985;French and Kline, 1989;Downer and Stoffolano Jr., 2006;Cilek and Olson, 2008 Cilek…”
Section: Pyramidal Trapmentioning
confidence: 99%
“…The average annual precipitation is 687 mm with a peak during May-June (data were provided by the Croatian Meteorological and Hydrological Service). Ecological studies have shown that horse fl ies are most active at pasture-forest ecotone near their developmental, host-seeking and resting sites (Baldacchino et al, 2013) and so traps were placed on the pasture at 60 m distance and parallel to the forest edge.…”
Section: Study Site and Trapsmentioning
confidence: 99%
“…Very few studies measuring trap effi ciency with horse fl ies have been completed (Mihok et al, 2006;Mihok & Carslon 2007;Van Hennekeler et al, 2008;Krčmar et al, 2014). Nzi, Box and Canopy traps have been used for catching horse fl ies in different fi eld studies (Krčmar et al, 2006(Krčmar et al, , 2010(Krčmar et al, , 2014Baldacchino et al, 2013), but a comparison and evaluation of trap efficiency has never been tested.…”
mentioning
confidence: 99%
See 1 more Smart Citation